New Facts about Varlam Cherkezishvilis Visit to Russian Empire in 1906 - Chkhaidze, Nodar (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2023)
The visit of Varlam Cherkezishvili to Russia in 1906 is known to Georgian historiography in some extent. Though whole range of details still need the clarification. In the paper we took an attempt to reveal new facts based on letters published in ‘Daily Chicago News’, archive materials and scholarly works. The investigation revealed that from February Cherkezishvili had been in Russian empire but not in Georgia. He only visited his home-land during the Spring and in Summer he went in a trip with his wife (we clarify this fact based on the letters of his wife – Frida. These letters are less known to Georgian historiography). We could not find out yet the purpose of this trip but we think that he visited Anarchist circles. The several new facts have been revealed about the ‘Georgian Relief Comittet ‘’. As it has been revealed this committee was restored after Bolshevik occupation of Georgia in 1921. The clarification of further details is the subject of future investigation.